PEMBERDAYAAN KULINER LOKAL DAN BUDAYA ORGANISASI NASI MANDHI RABEG BERBASIS CREATIVITY DIGITAL MARKETING OF VEGETARIAN FOOD DI KOTA CILEGON - Ranthy Pancasasti; Steven Ichal Rigel; Amalia Putri; Jessi Fitriani; Melliana Regita Susanti; Nadia Rizky Nurhaliza; Izan Fauzan; Rizka Maulana (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
During the current pandemic, the COVID-19 virus has worsened the state of the Indonesian economy. What's more, our society is required to be able to fulfill daily nutrition as a preventive measure from the Corona virus. So, in order to improve the basic nutrition of the community every day, the PPM team created a program based on Creativity Digital Marketing of Vegetarian Food with the theme of local culinary Rabeg Vegetarian and Nasi Mandhi. Before the PPM program was implemented, Rabeg from Cilegon was a culinary dish in the form of mutton stew that has a spicy taste. After the PPM program was implemented, Rabeg had a unique taste because it was made from soybeans in the form of tofu and tempeh combined with Rabeg spices. Meanwhile, Nasi Mandhi, before the PPM program was implemented, was in the form of spiced rice which was usually served with mutton or chicken. After the PPM program was implemented, Nasi Mandhi was combined with Vegetarian Rabeg as a meat substitute, as well as emping crackers and balado egg sauce as a complement. The method/approach used to manage the Vegetarian Rabeg and Nasi Mandhi is participatory, from planning to evaluation, which is carried out directly or indirectly, for example through seminars, coaching home industry owners for Vegetarian Rabeg and Nasi Mandhi. As well as information about local culinary rabeg and the process of making it through electronic media in the form of Instagram @kelclgraberian.